An Unmet Need: Surgical Gloves with Variable Finger Lengths - Ross Rudolph, MD, FACS; Christina Chopra, BA; Susan Van Etten, RN, MSN, PHN; Dale Glaser, PhD (Plastic and Reconstructive Surgery, Global Open, 2022)
Background:. Sterile gloves are essential for plastic surgery, but little research has been published on glove fit. Sterile gloves are produced by all manufacturers, with finger lengths fixed for all sizes. Many wearers have fingers that are shorter or longer than usual, causing functional limitations due to incorrect glove finger length and fingertip fit. Methods:. A multiquestion confidential electronic survey of glove finger length fit was sent to 6810 plastic surgery glove wearers from three organizations: American Society of Plastic Surgeons, International Society of Plastic and Aesthetic Nurses, and Association of Plastic Surgery Physician Assistants. Data were collected for this descriptive study in 2020–2021, and statistical analyses were performed using SPSS (version 27). Sample gloves from six brands were directly measured for finger length. Results:. The survey yielded 500 responses, with some respondents not answering all questions. The response rate from American Society of Plastic Surgeons members was 8.2%, and was 7.3% from all groups combined. The most common reason for glove finger length dissatisfaction was fingers being too long (41.61%). Although there was variation in measured glove finger lengths, the variation was not uniform. Of all responders, 28.6% were very likely, and 16.16%, moderately likely, to want to use gloves with longer or shorter fingers if available, constituting a total of 44. 76%. Of these, 36.55% would pay increased cost (10%–25%) for such gloves. Conclusions:. A high percentage of glove users would want gloves with variable finger lengths. Current surgical gloves do not support hand anatomy variations.